Attitudes of Vietnamese teachers of English in universities toward World Englishes in the classroom - Dương, Huyền Thắm (2020)
The growth of English worldwide has led to the emergence of English as a Lingua Franca (EFL) in English Language Teaching (ELT). This study concentrates on cognitive and behavioral aspects of teachers‘ attitude towards ESL and EFL A questionnaire was delivered to 111 teachers from seven state universities in Vietnam; a semi-structured interview then was carried out with eleven volunteer teachers. Data reveal the following phenomena which apply for both Outer and Expanding Circle varieties. First, the vast majority of Vietnamese teachers are aware of English varieties and/or implications of EFL/EIL in TESOL. Second, they express a positive opinion towards both Outer Circle and Expanding Circle varieties of English and the introduction of them to students. They also believe that it is important to introduce these varieties. Finally, the study indicates that teachers are likely to introduce these varieties to students but it depends on many variables. Implications of this study are expected to be beneficial for researchers, educators, and policy makers in ELT, especially in ELT in Vietnam